The Cytotoxic and Apoptotic Effects of Scrophularia Atropatana Extracts on Human Breast Cancer Cells - Elham Safarzadeh; Abbas Delazar; Tohid Kazemi; Mona Orangi; Dariush Shanehbandi; Solmaz Esnaashari; Leila Mohammadnejad; Saeed Sadigh-Eteghad; Ali Mohammadi; Mehrdad Ghavifekr Fakhr; Behzad Baradaran (Tabriz University of Medical Sciences, 2017)
Purpose: Breast cancer is the most frequent malignancy diagnosed in women both in developed and developing countries. Natural products especially those from herbal origin have high potential in producing drug components with a source of novel structures. The present study was designed to explore the cytotoxic effects and the cell death mechanism of Scrophularia atropatana extracts. Methods: MTT assay was employed to evaluate the cytotoxic activity of the extracts of S. atropatana on the MCF-7 as well as non-malignant cells. Furthermore, induction of apoptosis was evaluated by TUNEL assay, cell death detection ELISA, DNA fragmentation test, western blotting and Real Time PCR. Results: In vitro exposures of the MCF-7 cells with different concentration of S. atropatana extract significantly inhibited their growth and viability and induced apoptosis in the MCF-7 cells. Cleavage PARP protein, decrease in the mRNA expression levels of bcl-2 and increase expression of Caspase-3 and Caspase-9 mRNA, highlights that the induction of apoptosis was the main mechanism of cell death. Moreover the expression study of Caspase-9 mRNA showed that, the extracts have induced apoptosis via intrinsic mitochondrial pathway. Conclusion: Our results demonstrated that dichloromethane extract of Scrophularia atropatana has an apoptotic effects and it can be developed as anticancer agents.